THE DIASPORA OF PALEMBANGNESE ZURIAT IN MALUKU - Farida R Wargadalem; Nanda Julian Utama; Lukman Nadjamuddin (Sriwijaya University Learning and Education International Conference, 2018)
This paper is to provide an explanation and a description about the diaspora of Sultan Mahmud Badaruddin II and his descendants (Zuriat) descendants and his followers in Maluku islands. This study is limited to three regions; Ternate Island, Bacan Island, and Ambon City. The main problem in this research is what lies behind the occurrence of diaspora from zuriates of Sultan Mahmud Badaruddin II and his followers, and their roles in these three locations. Sultan Mahmud Badaruddin II (SMB II) was one of the greatest and the most prominent Sultan in Palembang Sultanate. In addition, he was also respected because he dared to oppose foreign parties, especially Dutch and British who were eager to seizing Palembang's natural wealth which known had dominated the trade of tin and pepper as the result it led to several wars with the Sultanate. This battle was won by Dutch, which resulted in capturing and exiling of the Sultan and his followers to Batavia (1821) and Ternate in 1822. It was the beginning of the exile of Palembangnese into Maluku Islands. The second exile took place in 1825, after the resistance led by Sultan Ahmad Najamuddin Prabu Anom, the son of Sultan Ahmad Najamuddin II. Fifty years later, the exile occurred again in the descendants of SMB II, and other Sultanate families. This second exile spread out to several points. It was the beginning of diaspora of Palembangnese zuriat began almost everywhere in Maluku Islands. It can be said that the concentration of the Palembangnese is more common in the three places mentioned above. They made relation, and created new cultural patterns. In addition, some of them are also considered important because they become ellites. It becomes the most interesting point to be discussed through a historical perspective, by prioritizing historical methodology and oral traditions that will become references as well as being the main source in this paper.